The Red and the Black: Images of American Indians in the Italian Political Landscape - Mariani, Giorgio (Studia Anglica Posnaniensia, 2018)
In Italy, over the last decades, both the Left and the Right have repeatedly employed American Indians as political icons. The Left and the Right, that is, both adopted and adapted certain real or often outright invented features of American Indian culture and history to promote their own ideas, values, and political campaigns. The essay explores how well-established stereotypes such as those of the ecological Indian, the Indian as victim, and the Indian as fearless warrior, have often surfaced in Italian political discourse. The “Indiani Metropolitani” student movement resorted to “Indian” imagery and concepts to rejuvenate the languages of the old socialist and communist left, whereas the Right has for the most part preferred to brandish the Indian as an image of a bygone past, threatened by modernization and, especially, by immigration. Indians are thus compared to contemporary Europeans, struggling to resist being invaded by “foreign” peoples. While both the Left and the Right reinvent American Indians for their own purposes, and could be said to practice a form of cultural imperialism, the essay argues that the Leftist appropriations of the image of the Indian were always marked by irony. Moreover, while the Right’s Indians can be seen as instances of what Walter Benjamin (1969) described as Fascism’s aestheticization of politics, groups like the Indiani Metropolitani tried to politicize the aesthetics.